Kirkpatrick's Evaluation Model for The Implementation of Industrial Standard GTAW Welding in Vocational Teacher Training Center - Farida, Khotimatul; Nurhadi, Didik (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2023)
The Vocational Teacher Training Center held industrial-based training by applying project-based learning to train Industrial Standard GTAW Welding. Then, this study was carried out to evaluate the effectiveness of training implementation of Industrial Standard GTAW Welding. This study used the Kirkpatrick Evaluation Model in reaction and learning levels. A questionnaire and interview were chosen to collect data. The data were analyzed by using descriptive technique, t-test, and qualitative data analysis with NVivo. The findings indicated that the participants' satisfaction scores in reaction and learning levels were very high. The assessment of the participants at the reaction level was seen from three perspectives: instructors’ reaction, reaction to the training delivery, and reaction to the training environment. Assessment of participants at the learning level was viewed from the impact of learning and knowledge training. The training proved that the program has been successful in developing the trainees’ skills. This also showed that the program has been running effectively. However, the final products from trainees did not meet the industry's standards. Optimizing this training requires additional time and standardization of participants' abilities using portfolios from training candidates. Balai Diklat Guru SMK menyelenggarakan pelatihan berbasis industri dengan menerapkan pembelajaran berbasis proyek untuk melatih Pengelasan GTAW Standar Industri. Kemudian penelitian ini dilakukan untuk mengevaluasi efektivitas pelaksanaan pelatihan Pengelasan GTAW Standar Industri. Penelitian ini menggunakan Model Evaluasi Kirkpatrick pada tingkat reaksi dan pembelajaran. Kuesioner dan wawancara dipilih untuk mengumpulkan data. Data dianalisis dengan menggunakan teknik deskriptif, uji-t, dan analisis data kualitatif dengan NVivo. Temuan menunjukkan bahwa skor kepuasan peserta pada tingkat reaksi dan pembelajaran sangat tinggi. Penilaian peserta pada tingkat reaksi dilihat dari tiga sudut pandang yaitu reaksi instruktur, reaksi terhadap penyampaian pelatihan, dan reaksi terhadap lingkungan pelatihan. Penilaian peserta pada tingkat pembelajaran dilihat dari dampak pembelajaran dan pelatihan pengetahuan. Pelatihan tersebut membuktikan bahwa program ini berhasil mengembangkan keterampilan peserta pelatihan. Hal ini juga menunjukkan bahwa program tersebut telah berjalan efektif. Namun, produk akhir dari peserta pelatihan tidak memenuhi standar industri. Dalam mengoptimalkan pelatihan ini memerlukan tambahan waktu dan standarisasi kemampuan peserta dengan menggunakan portofolio dari calon peserta pelatihan.